Answer:
y =
- 1
Explanation:
Given
a(y + 1) = b ( divide both sides by a )
y + 1 =
( subtract 1 from both sides )
y =
- 1
or alternatively
distribute the left side
ay + a = b ( subtract a from both sides )
ay = b - a ( divide both sides by a )
y =
![(b-a)/(a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5i7fsx4s51117ajtng2hdyvsm64t9uycv2.png)
Note y =
- 1 =
![(b-a)/(a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5i7fsx4s51117ajtng2hdyvsm64t9uycv2.png)